Sustained censorship in EG (2026-04) (Egypt) - Voidly (2026)
CRITICAL severity censorship detected in Egypt. Confidence: 80%. Data sourced from OONI.
Censorship Incident ID: EG-2026-0422
Keywords: censorship; EG; censorship; critical